Enhancing Karonese Youth Development in Regaji Village Through Volleyball - Sofyan, Rudy; Ginting, Junita Setiana; Tarigan, Bahagia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The young generation is very vulnerable to negative associations, especially those related to drug abuse. One of the ways to save the young generation from the harmful effects of such drug abuse is encouraging them to get engaged in sports or physical activities, such as volleyball. This study aims at: (i) describing the facilities needed to make the local youth in Regaji Village engaged in playing volleyball; and (ii) finding out the advantages of playing volleyball in enhancing the local youth development in Regaji Village. This study used a descriptive qualitative method to describe the phenomenon of volleyball games among youth in Regaji Village, Karo Regency, North Sumatra Province, Indonesia. The data were collected using direct observations and interviews. The data were analyzed qualitatively. The results show that the facilities available for playing volleyball in Regaji Village are not decent; meanwhile, many local young people like playing volleyball. Playing volleyball provides many advantages to help develop the youth potentials in Regaji Village. Attentions and concerns from the society members and the local government are required to attract more and more young generation in Regaji Village to get engaged in playing volleyball.